Finite element analysis of thermally actuated medical stent and staple implants using shape memory alloy. (2017) - Dahmardeh, Mahyar; Setarehdan, Seyed Kamaledin
In this paper, a thermally actuated medical stent and staple using shape memory alloy (SMA) are designed, numerically analysed, and compared to similarly designed stents and staples made of 316L stainless steel and Co-Cr alloy. The numerical analysis was carried out using finite element method. A consistent 3D model is used to investigate the effect of materials on the performance of the stent and staple. This study takes into account the interaction between the stent/staple and the in vivo environment, by modelling the in vivo environment forces. The results are in good agreement with those reported in the literature. According to the results, it can be concluded that when these three commercially available materials undergo an external force, SMA yields much better results in terms of maximum displacement under the same amount of stress. Especially when undergoing large loads, the SMA produces considerably more displacement than 316L stainless steel and Co-Cr, which suggests that using SMA is a promising path to make biomedical stents and staples.